Biofilm carrier type affects biogenic sulfur-driven denitrification performance and microbial community dynamics in moving-bed biofilm reactors. (January 2022) - Kostrytsia, Anastasiia; Papirio, Stefano; Khodzhaev, Murod; Morrison, Liam; Collins, Gavin; Lens, Piet N.L.; Ijaz, Umer Zeeshan; Esposito, Giovanni
Abstract: Autotrophic denitrification with biosulfur (ADBIOS) provides a sustainable technological solution for biological nitrogen removal from wastewater driven by biogenic S 0, derived from biogas desulfurization. In this study, the effect of different biofilm carriers (conventional AnoxK™ 1 and Z-200 with a pre-defined maximum biofilm thickness) on ADBIOS performance and microbiomics was investigated in duplicate moving bed-biofilm reactors (MBBRs). The MBBRs were operated parallelly in continuous mode for 309 days, whilst gradually decreasing the hydraulic retention time (HRT) from 72 to 21 h, and biosulfur was either pumped in suspension (days 92–223) or supplied in powder form. Highest nitrate removal rates were approximately 225 (±11) mg/L·d and 180 (±7) mg NO3 − -N/L·d in the MBBRs operated with K1 and Z-200 carriers, respectively. Despite having the same protected surface area for biofilm development in each MBBR, the biomass attached onto the K1 carrier was 4.8-fold more than that on the Z-200 carrier, with part of the biogenic S 0 kept in the biofilm. The microbial communities of K1 and Z-200 biofilms could also be considered similar at cDNA level in terms of abundance (R = 0.953 with p = 0.042). A relatively stable microbial community was formed on K1 carriers, while the active portion of the microbial community varied significantly over time in the MBBRs using Z-200 carriers. Graphical abstract: Image 1 Highlights: Denitrification rate and NO2 − accumulation differed depending on the carrier type. The biofilm mass on K1 carriers was 4.8 times higher than that on Z-200 supports. The same species were present in K and Z studies but they differed in abundances. The active microbial community varied significantly over time in MBBR with Z-200. More microorganisms were associated with process failure for Z-200 than K1 biofilms.